The Kedung Gede Tourism Village Recovery Plan (Post Pandemi Covid-19) - Rizki Nurul Nugraha (Westscience Press, 2023)
This research is motivated by the covid-19 pandemic which has a major impact on the tourism sector and recovery efforts are needed to increase the number of tourist visits after the covid-19 pandemic. This research aims to analyze the tourism potential and development of kedung gede tourist village as covid-19 in the post-pandemic and the benefits felt by the surrounding community from the development of kedung gede tourist village itself. This research uses a descriptive qualitative approach to get a complete picture of Kedung Gede Tourism Village with the analysis method used is SWOC analysis. Primary and secondary data obtained came from observations, interviews, documentation and literature studies, such as journals, books, reports. The results of research conducted using SWOC provide several strategies such as: 1) Reviving local traditions periodically to create an attractive tourism attraction. 2) Increase the number of homestays and improve their quality standards in order to become an attractive and quality tourist attraction. 3) Building a unique tourism identity by developing a distinctive icon of Kedung Gede Tourism Village that is different from other tourism villages, 4) Building a network of cooperation with government and private agencies to get support in procuring and improving tourism support facilities and improving road accessibility to the tourism village.